The Influence of Social Support on Entrepreneurial Inclination among Business Students in Indonesia - Sahban, Muhammad Amsal; Ramalu, Subramaniam Sri; Syahputra, Ruswiati (Information Management and Business Review, 2016)
The objective of this study is to investigate the influence of social support on student’s inclination toward entrepreneurship. It also aims to test whether gender can moderate the relationship between SS and entrepreneurial intention among business students in Indonesia. Quantitative analysis was conducted using SPSS version 22. This study conveniently distributed 1,230 self-administrated questionnaires to the business students at public and private universities in Indonesia. This data collection process yielded back with 381 usable responses that were used in the statistical analysis for assessing the relationship between SS and EI as well asthe difference between male and female students in terms of entrepreneurial intention.This study reveals that, there is a positive relationship between social support system and student’s inclination toward entrepreneurship and there is a difference between male and female students in terms of entrepreneurial intention.